The Definition of African Literature: Devoid of Self-Respect, Self-Assertion: Challenges and Responsibilities in Defining African Literature (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The African continent has been devoid of self-respect, self-assertion and devoid from the right to express itself and this is essentially the definition of the African literature. The discrimination further requires for certain principles to be adopted hereby. Karl Marx has not dealt with any particular idea about it but It is all to say that since it is a perpetual trauma of suffering, it is the duty of the writer to explain the defetishizing of the continent and to find a way to respectable utterances.